Toll-like receptors as targets for allergen immunotherapy. Issue 6 (December 2015) - Unknown
Abstract : Purpose of review: Toll-like receptors (TLRs) are novel and promising targets for allergen immunotherapy. Bench studies suggest that TLR agonists reduce Th2 responses and ameliorate airway hyper-responsiveness. In addition, clinical trials are at initial phases to evaluate the safety and efficacy of TLR agonists for the allergen immunotherapy of patients with allergic rhinitis and asthma. Recent findings: To date, two allergy vaccine-containing TLR agonists have been investigated in clinical trials; Pollinex Quattro and AIC. The former contains monophosphoryl lipid, a TLR4 agonist and the latter contains, CpG motifs activating the TLR9 cascade. Preseasonal subcutaneous injection of both of these allergy vaccines has been safe and efficacious in control of nasal symptoms of patients with allergic rhinitis. CRX-675 (a TLR4 agonist), AZD8848 (a TLR7 agonist), VTX-1463 (a TLR8 agonist) and 1018 ISS and QbG10 (TLR9 agonists) are currently in clinical development for allergic rhinitis and asthma. Summary: TLR agonists herald promising results for allergen immunotherapy of patients with allergic rhinitis and asthma. Future research should be directed at utilizing these agents for immunotherapy of food allergy (for instance, peanut allergy) as well.